Immobilized heterogeneous catalysts for CO2 hydrogenation to formic acid: A review - Hongwei Li; Bo Peng; Shuaishuai Lv; Qiuming Zhou; Zhennan Yan; Xuebin Luan; Xuandong Liu; Congcong Niu; Yanfang Liu; Jili Hou; Zhiqiang Wang; Ying Chen; et al. (Carbon Capture Science & Technology)
Formic acid is a promising hydrogen storage medium that can be produced via the catalytic hydrogenation of CO2. Compared with heterogeneous catalysts, homogeneous catalysts composed of organic metal complexes, especially Ru- and Ir-based catalysts, show higher activity and selectivity for the catalytic reaction of CO2 hydrogenation to formic acid; however, it is difficult to separate them from the reaction products. Heterogeneous catalysts prepared by immobilizing metal complexes onto solid materials demonstrate high activity and selectivity, similar to homogeneous catalysts, and solve the problem of catalyst separation. For preparing such catalysts, the choice of support is particularly important because effective anchoring is the key to realize catalyst recycling. Supported heterogeneous catalysts are mainly based on inorganic oxides and porous polymers (e.g., metal-organic frameworks, covalent organic frameworks, and organic polymers). This review comprehensively examines the advancements in immobilized heterogeneous catalysts for the hydrogenation of CO2, focusing on support materials, reaction mechanisms, catalyst immobilization conditions, and the impact of various reaction conditions on catalytic performance. Furthermore, we provide a comparative analysis of immobilized catalysts and their homogeneous counterparts, underlining the advantages of site isolation and the role of support materials in enhancing catalytic activity. The design and development of immobilized heterogeneous catalysts are important in the field of CO2 hydrogenation to formic acid because of their abundant active sites, excellent catalytic stability, flexible chemical modifiability, and low preparation cost. We conclude with perspectives on future research directions, emphasizing the need for innovative catalyst designs and optimization of reaction conditions to achieve sustainable and economically viable CO2 hydrogenation processes.